Decision making in dental implantology : atlas of surgical and restorative approaches - Tosta, Mauro; Moura Filho, Gastao Soares de; Chambrone, Leandro (Hoboken, NJ : Wiley, 2017)
Decision Making in Dental Implantology: Atlas of Surgical and Restorative Approaches offers an image-based resource to both the surgical and restorative aspects of implant therapy, presenting more than 2,000 color images with an innovative case-by-case approach. -Takes a highly pictorial approach to all aspects of implant dentistry -Discusses both the surgical and restorative aspects of implant therapy in a single resource -Describes a wide range of clinical scenarios likely to be encountered in daily practice -Covers anterior, posterior, and full-mouth restorations -Presents more than 2,000 color images showing the basic concepts and clinical cases.
Current status of clinical practice with dental implants : an evidence-based decision making overview -- Treatment planning for bone defects in the alveolar ridge -- Treatment of esthetic areas -- Treatment of posterior areas -- Implant-supported rehabilitation of completely and partially edentulous patients -- Multidisciplinary decision-making : the complexity of some potential'real-world' clinical scenarios.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Dental Implants; MEDICAL / Surgery / General; Dental implants; Dental Implantation; Reconstructive Surgical Procedures; Electronic books